Seasonal dynamics of the fractional composition of forest litter of Holosiivskyi National Nature Park - Пилипчук Т.; Тесьолкіна Т.; Лукашов Д. (Київський національний університет імені Тараса Шевченка, 2019)
Leaf litter is an important structurally fucnctional element of forest ecosystem, dynamic processes in which create a connection between phytocenosis and edaphotope. Accumulation of litter material and its decomposition rate characterize intensity of substance circulation in forest ecosystem. The present article deals with the results researching of the peculiarities of the forming and decomposition of soil litter layer in the hornbeam oak in the conditions of Holosiivskyi National Nature Park (Kyiv) were examined. Its considerable sizes on the north slope of ravine coast system (16,4 t/ha in autumn, 4,3 t/ha in the summer) were determed. Analysis of litter supply at the end of abscission showed a lack of significant differences in different sections of the terrain (12,3–16,4 t/ha). During the winter period, litter volumes are significantly reduced due to intensive mineralization processes under the snow cover. Most intensively, these processes take place in areas of the slope. Fractional composition of the litter did not generally depend on the location of the experimental area by relief elements. A dominating faction in autumn and spring was fall (65–69 % of the total mass). In the summer, a portion of dust (38-46 %) increased. The smallest number of branches was observed in autumn and winter, their scope was between 11-22 % in all research areas. The maximum amount of branches was observed at all areas in the summer. Their volume was 27-49 %. The scope of seeds and its residues was insignificant and amounted to 1-3 % during the year. The speed of mineralization of cellulose by an application method with the use of filter paper is determined. The rate of decomposition of cellulose in the conditions of the southern and northern ravine slope turned out to be similar to the maximum in March and July-August.

Лісова підстилка – важливий структурно-функціональний елемент лісових екосистем, динамічні процеси в якому утворюють зв'язок між фітоценозом та едафотопом. Накопичення підстилкового матеріалу та швидкість його розкладу характеризує інтенсивність круговорота речовин у лісових екосистемах. Розглянуто особливості формування і розкладу підстилкового шару ґрунту в грабовій діброві в умовах Національного природного парку "Голосіївський" (м. Київ). Встановлено значні її обсяги на північному схилі яружної берегової системи (16,4 т/га восени, 4,3 т/га влітку). Аналіз запасів підстилки на момент закінчення листопаду показав відсутність суттєвих відмінностей на різних ділянках рельєфу (12,3–16,4 т/га). Протягом зимового періоду обсяги підстилки суттєво зменшуються за рахунок інтенсивних процесів мінералізації під сніговим покривом. Найбільш інтенсивно ці процеси відбуваються на ділянках схилу. Фракційний склад підстилки в цілому також не залежав від розташування дослідної ділянки за елементами рельєфу. Домінуючою фракцією восени та навесні був листовий опад (65-69 % загальної маси). Влітку зростала частка трухи (38-46 %). На всіх дослідних ділянках найменша кількість гілок спостерігалась восени і взимку, їхня частка була в межах 11-22 %. Максимальний обсяг гілок спостерігався на всіх ділянках влітку. Їхній обсяг становив 27-49 %. Частка насіння і його залишків протягом року була незначною і становила 1-3 %. Визначено швидкість мінералізації целюлози аплікаційним методом із застосуванням фільтрувального паперу. Динаміка швидкості розкладання целюлози в умовах південного та північного схилів яру виявилася подібною з максимумом у березні та липні-серпні. На ділянці плакору швидкість розкладу целюлози характеризувалася значною динамікою без чітко визначених сезонних періодів.
Сезонна динаміка фракційного складу лісової підстилки НПП "Голосіївський"
Keywords: litter; fall; mineralization; підстилка; опад; мінералізація